2018
DOI: 10.1186/s12889-018-6158-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on voluntary medical male circumcision in a low uptake setting in northern Uganda

Abstract: BackgroundFree VMMC services have been available in Uganda since 2010. However, uptake in Northern Uganda remains disproportionately low. We aimed to determine if this is due to men’s insufficient knowledge on VMMC, and if women’s knowledge on VMMC has any association with VMMC status of their male sexual partners.MethodsIn this cross sectional study, participants were asked their circumcision status (or that of their male sexual partner for female respondents) and presented with 14 questions on VMMC benefits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
4
15
2
Order By: Relevance
“…This study was a sub-study of a research that was looking at the correlates of VMMC uptake in northern Uganda. Two other papers that looked at knowledge, enhancers and barriers of VMMC uptake in this region have already been published 11 , 12 . After answering that question, the study further wanted to know why the people in Gulu especially men did not seek VMMC services which were being offered at no cost both at static and mobile (out - reaches or camps) sites within their communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was a sub-study of a research that was looking at the correlates of VMMC uptake in northern Uganda. Two other papers that looked at knowledge, enhancers and barriers of VMMC uptake in this region have already been published 11 , 12 . After answering that question, the study further wanted to know why the people in Gulu especially men did not seek VMMC services which were being offered at no cost both at static and mobile (out - reaches or camps) sites within their communities.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were administered in a respondent's preferred language. The questions analyzed for this manuscript were about perception of increased risk of HIV infection though the other questions were mainly about knowledge of VMMC messages and has already been published 11 . Systematic sampling was used to select households using lists that had been used earlier during a mosquito net distribution campaign.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, perceived severity such as bleeding and infection, irritation of the glans, injury to the penis and increased Meatitis made uptake of safe male circumcision services low [9]. Uganda's scenario of uptake of safe male circumcision is not far different from other countries in the region, up take is still low despite being free [10]. The country's target by 2015 was to circumcise 4.2 million adults, however, required an effective model to achieve [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research done on the uptake of VMMC amongst males has shown that several barriers and drivers hinder and influence the uptake of VMMC by males (Hankins et al, 2016; Nanteza et al, 2018; Rodriguez et al, 2019). Among these are: (1) individuals’ perceptual factors related to fear of pain, procedural complications, and fear of the HIV testing; (2) social factors such as norms, values, and cultural and religious beliefs; (3) social influences such as female partner roles, the media and other public figures, and role models (Abunah et al, 2016; Jones et al, 2018; Nanteza et al, 2018; Osaki et al, 2015; Rodriguez et al, 2019; Wambura et al, 2017).…”
mentioning
confidence: 99%